3^x+2 + 3^x - 23 = 949 - 2 × 3^x
GIÚP MK VỚI
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\Leftrightarrow\left[3x+6-23\right]\cdot\left(9-8+20\cdot0\right)=147\)
=>3x=164
hay x=164/3
\(a,\frac{23}{15}-\frac{2}{3}x=0,2\)
\(\frac{2}{3}x=\frac{4}{3}\)
\(x=2\)
\(b,\frac{x}{3}=\frac{2}{3}+\left(\frac{-1}{7}\right)\)
\(\Rightarrow\frac{x}{3}=\frac{11}{21}\)
\(\Rightarrow x.21=3.11\)
\(\Rightarrow21x=33\)
\(\Rightarrow x=\frac{11}{7}\)
a. \(\frac{23}{15}-\frac{2}{3}x=0,2\)
\(\frac{23}{15}-\frac{2}{3}x=\frac{1}{5}\)
\(\frac{2}{3}x=\frac{23}{15}-\frac{1}{5}\)
\(\frac{2}{3}x=\frac{4}{3}\)
\(x=\frac{4}{3}:\frac{2}{3}\)
\(x=2\)
Vậy \(x=2\)
b. \(\frac{x}{3}=\frac{2}{3}+\frac{-1}{7}\)
\(\frac{x}{3}=\frac{11}{21}\)
\(\frac{7x}{21}=\frac{11}{21}\)
\(\Rightarrow7x=11\)
\(x=11:7\)
\(x=\frac{11}{7}\)
Vậy\(x=\frac{11}{7}\)
a) 5(x+7) - 10 = 2^3 . 5
5(x+7 ) -10 = 8 . 5 = 40
5(x+7) = 40 + 10 = 50
x + 7 = 50 : 5 = 10
x = 10 - 7 = 3
\(\text{(x + 2)^3 - 41 = 23}\\ \left(x+2\right)^3=23+41\\ \left(x+2\right)^3=64\\ x+2=4\\ x=4-2\\ x=2\)
Lời giải:
$(x+2)^3-41=23$
$\Leftrightarrow (x+2)^3=23+41=64=4^3$
$\Leftrightarrow x+2=4$
$\Leftrightarrow x=2$
\(\left(3x+2\right)\left(x-1\right)+\left(x+3\right)\left(x-7\right)+2x+23=0\\ \Leftrightarrow3x^2+2x-3x-2+x^2+3x-7x-21+2x+23=0\\ \Leftrightarrow3x^2-x^2+2x-3x+3x-7x+2x-2-21+23=0\\ \Leftrightarrow x^2-3x=0\\ \Leftrightarrow x.\left(x-3\right)=0\\ \Leftrightarrow\left[{}\begin{matrix}x=0\\x-3=0\end{matrix}\right.\)
<=> x=0 hoặc x=3
(3x+2)(x-1)+(x+3)(x-7)+2x+23=0
=>3x2+2x-3x-2+x2+3x-7x-21+2x=-23
=>(3x2+x2)+(2x-3x+3x-7x+2x) -(2+21)=-23
=>4x2-3x-23=-23
=>4x2-3x=-23+23=0
=>x(4x-3)=0
=>x=0 hoặc 4x-3=0
=>x=0 hoặc x=3/4.
3\(^{x+2}\) + 3\(^{x}\) - 23 = 949 - 2 x 3\(^{x}\)
3\(^2.\)3\(^{x}\) + 3\(^{x}\) + 2.3\(^{x}\) = 949 + 23
3\(^{x}\).(9 + 1 + 2) = 97
3\(^{x}\).(10 +2) = 97
3\(^{x}\).12 = 97
3\(^{x}\) = 97 : 12
3\(^{x}\) = 81
3\(^{x}\) = 3\(^4\)
\(x=4\)
Vậy \(x=4\)